Guidelines for diagnosis, staging and treatment of metastatic colorectal cancer by Grupo Español Multidisciplinar en Cancer Digestivo (GEMCAD). (April 2015) - Aguilar, Guadalupe; Albiol, Santiago; Alcaide, Julia; Alonso, Martina; Alonso, Vicente; Andreu, Montserrat; Aparicio, Jorge; de la Vega, Fernando Arias; Arrivi, Antonio; Ayuso, Juan Ramón; Bohn, Uriel; Bouzas, Rosa; et al.
Abstract : Advances in the care of patients with metastatic colorectal cancer arise from well-designed clinical trials. In the present document we address specific challenges in the design of clinical trials for metastatic colorectal cancer regarding staging and standard of care according to prognosis, as well as some relevant methodological issues.